Dramatic composition elements in monodrama texts (Journal of the College of Basic Education, 2022)
Dramatic composition elements in monodrama textsAssist.Lect. Ziad Helou JadallahTikrit University / College of Education for Human SciencesZiad.Helu@gmail.com07706636518 ABSTRACT: Dramatic composition and its elements are among the renewed topics in theater because they are renewable with all modern theatrical currents and trends, and with this, we find elements of composition in (monodrama) have carved a trend that made them worth research and study, until the study was divided into four chapters, the first chapter came under the title ( Methodological framework) and included the research problem, the need for it, the importance of research, the objectives of the research and the limits of the research. The chapter was concluded by specifying the most important terms, and the second chapter was divided(The theoretical framework) in two topics, the first one is the elements of the dramatic formation and the second one includes the elements of theatrical construction, while the third chapter includes the research procedures as a sample was chosen, which is the text of a monodrama (the last news), and the fourth chapter concerned the results and conclusions and the list of sources and references and the research came out with a number of results The most prominent conclusions are:1- The dramatic structure does not take a hierarchical shape as in the structure drawn by (Freitaj) (but rather begins (monodrama) from a point and ends there, so it is more like the structure of the absurd.2- There is no opponent to fuel conflict in its traditional sense, but rather an opponent is created by the personality that makes anyone who opposes its ideas an opponent in some way.